Training on Preparing a Balanced Nutritional Food Menu During Fasting for Cheerful Mutiara Cadres of Sungai Andai, Banjarmasin City - Ari Widyarni; Elsi Setiandari Lely Octaviana; M. Bahrul Ilmi; Edy Ariyanto; Netty Netty; Husnul Khatimatun Inayah; Noorhidayah Noorhidayah; M. Febriza Aquarista (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Fasting is practiced by Muslims, especially during the month of Ramadan. Fasting is believed tohave numerous benefits and is a form of therapy (fasting therapy) for curing several degenerativediseases. People in Banjarmasin City often eat foods high in fat and sugar during fasting, andmany use excessive amounts of food coloring and flavoring. Lack of knowledge about healthyeating habits during fasting is a factor that can affect health. This has resulted in an increase indegenerative diseases such as hypertension, cholesterol, heart disease, and diabetes mellitus. Thiscommunity service program aims to improve the knowledge and skills of mothers, who play a rolein providing food for their families and developing nutritious diets, based on the awareness of theimportance of balanced nutrition according to the